Maritime Mobility of Music Features within South and Southeast Asia - Jähnichen, Gisa (Cultural Arts Research and Development, 2024)
The maritime routes in and between South and Southeast Asia were the main routes of the first interconnections leading to current globalization effects among different locations in the area using the sea as transportation basis. It is very important to not only follow migration routes, but mainly trade routes to understand these first steps. This joint paper is based on intense field and literature research on the given topic and various examples. It is rather describing the historical outline and gives an overview on existing statements. The main focus is the emerging transcendency between people living in this region and their deriving outcomes over a longer period of time.